Micelle‐to‐vesicle transition of lipoamino Gemini surfactant induced by metallic salts and its effects on antibacterial activity - Pachon Gomez, Erica Marcela (2022)
Gemini surfactants are amphiphilic molecules formed by two polar heads and two hydrophobic tails joined by a spacer between the polar groups. Their molecular structure gives them particular physico-chemical properties in comparison with their monomeric counterparts. In this work we synthetized a Gemini surfactant (SDDC) derived from the amino acid cystine and decanoic acid. The influence of different metallic salts on the aggregation of the surfactant was studied. SDDC forms core–shell type triaxial ellipsoidal micelles in aqueous solution, but the aggregates suffer a change in morphology, forming vesicles in the presence of copper or silver ions. This behavior was corroborated by TEM and SAXS measurements. With the last technique was possible to estimate that vesicles formed in presence of copper consisted of 7.3 stacked bilayers. It was possible to determine that Cu2+ was reduced to Cu+ in the solution containing SDDC, through EPR and UV–visible spectrophotometry measurements. The reduction of copper was accompanied with the concomitant oxidation of the cystine. The antimicrobial activity of the different aggregates was studied against E. coli and S. aureus and compared with the conventional antibiotic ampicillin. The most efficient system resulted the mixture of SDDC:CuSO4/10:1 against the Gram-negative bacterium, there with the minimum concentration used (0.01 mM) was possible to inhibit 70 % of growth. The new systems characterized in this work have many possibilities for potential applications, mainly in the area of drug delivery systems, templates in the synthesis of nanomaterials or as antibacterial compounds.